Pengaruh Penggunaan Media Digital Flipbook terhadap Hasil Belajar Siswa Kelas V Materi Bilangan Pecahan Matematika Sekolah Dasar - Rindy Ayu Angelia; Navatika Vivayosa Br Surbakti; Alfredo Batubara; Syahrial Syahrial (Lembag, 2024)
This study aims to determine the effect of using digital flipbook media in improving the understanding of grade v students on mathematical integers in elementary school. This research is a quantitative research. This research uses an experimental method with an initial test design (pre-test) and a final test (post-test) used in two groups, namely the control group and the experimental group. The study population was all fifth grade students. The research sample was 60 students who were divided into two groups of 30 students each with simple random sampling technique. Data collection techniques through interviews, learning outcomes tests, learning motivation questionnaires and documentation. As for data analysis techniques using normality test, homogeneity test, and hypothesis testing with the right party t test formula and two-party t test. The average posttest in the experimental class> control class (82.5> 74.6). The results of the t-test of student learning outcomes obtained data significance ≤ 0.05 which shows digital flipbook learning media affect student learning outcomes on fractional number material. The correlation test results obtained rcount = 0.645 (strong category) so that there is a positive correlation between motivation and student learning outcomes. So it is stated that there is a positive and significant influence of the use of digital flipbook media on student motivation and learning outcomes in elementary school math fractions.